MODULAR ERRORS CORRECTION BASED ON COMPOSITE cyclic codes - E. G. Makeichik; V. K. Kanapelka; A. I. Korolev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The effectiveness evaluation of the proposed method for correction modular and burst errors based on composite and cyclic codes and step encoding and decoding of information is made. The main parameters of the channel codecs are detected and a comparative analysis of the calculated characteristics with channel codec parameters based on the known (basic) codes is realized. It's shown that for practical purposes it's sufficient to use the ratio of internal information symbol interleaving and decoding stages of encoding no more than two or three stages.